The Determinants and Performance Impact of Outside Board Leadership - Balsam, Steven; Puthenpurackal, John; Upadhyay, Arun (Journal of Financial and Quantitative Analysis, 2016)
Outside board chairs are more likely in firms that are smaller, have greater stock volatility and research and development intensity, and have a lower proportion of inside directors and less institutional ownership; they are also more likely when chief executive officers have shorter tenure and lower ownership. We also find that the existence of an outside chair is associated with geographical and industry norms. An outside chair is positively associated with firm performance, a finding robust to various estimation methods, including event study and multivariate analyses incorporating controls for endogeneity, as well as market and accounting measures of performance. We note, however, that the relationship between outside chair and firm performance varies with firm characteristics.